To work or to study? Postmigration educational investments of adult refugees in Germany - evidence from a choice experiment - Andreas Damelang; Yuliya Kosyakova (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
In this article, we analyze individual factors and situational conditions under which immigrants are more or less likely to invest in host country-specific human capital. Theoretically, we root our expectations in a strand of the immigrant human capital investment model combined with a basic model of educational decisions. Using a choice experiment, we simulate a decision process among refugees in Germany and examine the determinants of investment decisions into host country-specific credentials such as vocational education. The choice experiment was introduced in the IAB-BAMF-SOEP Survey of Refugees (2020), a representative longitudinal survey of recently arrived refugees in Germany. We find that refugees' probability of investing in vocational education is guided by the transferability of foreign human capital, the time horizon to reap investments, and rational cost-benefit considerations. The probability of success is influential on its own but also bolsters the relevance of costs and benefits in educational choices. – – In diesem Artikel analysieren wir individuelle Faktoren und situative Bedingungen, unter denen Einwanderer mehr oder weniger wahrscheinlich in aufnahmeland-spezifisches Humankapital investieren. Theoretisch stützen wir unsere Analysen auf einen Ansatz des Humankapital-Investitionsmodells von Zuwanderern und verbinden diesen mit einem Basismodell für rationale Bildungsentscheidungen. Mit Hilfe eines Choice-Experiments simulieren wir einen Entscheidungsprozess unter Flüchtlingen in Deutschland und untersuchen die Determinanten von Investitionsentscheidungen in aufnahmeland-spezifische Qualifikationen wie z.B. Berufsausbildung. Das Choice-Experiment wurde im Rahmen des IAB-BAMF-SOEP-Flüchtlingssurvey (2020) durchgeführt, einer repräsentativen Längsschnittbefragung von neu nach Deutschland gekommenen Flüchtlingen. Die Ergebnisse zeigen, dass sich die Wahrscheinlichkeit von Flüchtlingen, in berufliche Bildung zu investieren, an der Übertragbarkeit von ausländischem Humankapital, dem Zeithorizont für Investitionen und rationalen Kosten-Nutzen-Überlegungen orientiert. Die Erfolgswahrscheinlichkeit der Investition ist für sich selbst maßgebend, verstärkt aber auch die Bedeutung von Kosten und Nutzen bei Bildungsentscheidungen.
Keywords: I24; I26; J24; J61; F22; 330; Choice experiment; immigrant human capital investment; refugees; IAB-BAMF-SOEP Survey of Refugees in Germany